Komparasi Degree of Risk Asuransi Syariah vs Konvensional - Mu’awanah, Mu’awanah; Mu’awwanah, Uliyatul (INAIFAS Press, 2021)
In its development, the Islamic Finance Industry is growing rapidly. One of the non-bank Islamic financial institutions is an insurance company, the company carries out its function as a service provider institution for participants or policy holders by managingfunds tabarru and then redistributing them in the form of guarantees against certain risks using principles that are in accordance with Islamic Sharia. The fundamental thing that is the distinguishing factor between the Islamic and conventional insurance systems is that there is amechanism risk sharing. One advantage compared to themechanism risk transfer because it is in line with the principle of helping. The purpose of the study is to see a comparison between life insurance Islamic and conventionalproducts in terms of the degree of risk and how big the significance of the difference in risk is. The method used in this study uses a quantitative approach obtained from primary data in the form of premium reports and claims obtained from the Bumiputera Syariah insurance company and Equity insurance. The data analysis technique uses probability theory and data analysis uses